(untitled) (Journal of Applied Oral Science, 2021)
Adding a biological apatite layer to the implant surface enhances bone healing around the implant. Objective: This study aimed to characterize the mechanical properties and test human gingival fibroblasts behavior in contact with Zirconia and Titanium bioactive-modified implant materials. Methodology: 6 groups were considered: Titanium (Ti6Al4V), Ti6Al4V with 5% HA and 5% ßTCP, Zirconia (YTZP), YTZP with 5% HA and 5% ßTCP. For each group, we produced discs using a novel fabrication method for functionally graded materials, under adequate conditions for etching and grit-blasting to achieve equivalent surface microroughness among the samples. Surface roughness (Ra, Rz), water contact angle, shear bond strength, and Vickers hardness were performed. Human gingival fibroblasts immortalized by hTERT gene from the fourth passage, were seeded on discs for 14 days. Cell viability and proliferation were assessed using a resazurin-based method, and cellular adhesion and morphology using field emission gun scanning electron microscopy (FEG-SEM). After 3 days of culture, images of fluorescent nucleic acid stain were collected by confocal laser scanning microscopy (CLSM). Results: Results were presented as mean ± standard deviation (SD). We compared groups using one-way ANOVA with Tukey’s post-hoc test, and significance level was set at p<0.05. After 14 days of culture, cell viability and proliferation were significantly higher in YTZP group than in other groups (p<0.05). Samples of YTZP-ßTCP presented significantly higher wettability (p<0.05); yet, we observed no improvement in cell behavior on this group. Fibroblast spreading and surface density were more evident on YTZP specimens. Adding calcium-phosphate bioactive did not alter the tested mechanical properties; however, Ti6Al4V material shear bond strength was statistically higher than other groups (p<0.05). Conclusion: Adding bioactive materials did not improve soft-tissue cell behavior. When compared to other zirconia and titanium groups, pure zirconia surface improved adhesion, viability and proliferation of fibroblasts. Cell behavior seems to depend on surface chemical composition rather than on surface roughness.